(untitled) (City: History, Culture, Society, 2020)
The article deals with the robbery of Holocaust victims in three small towns in Western Volhynia: Dubrovytsia, Korets, and Kostopil. In addition to financing the German military regime and enriching the Germans, the robbery of the victims here served to legitimize the genocide among the local population and encourage it to collaborate. The research has managed to establish that economic factors motivated the behaviour of a part of the local population during the organization of the crime in Kostopil, Korets, and Dubrovytsia. At the initial stage, the inhabitants of these towns joined the plundering of their Jewish neighbours during the pogroms in late June – early July 1941. During the creation of the ghetto, legalized by the Nazi occupying authorities, spontaneous looting of the victims’ dwellings and trafficking of their property (mainly clothing and household items) took place. During the ghetto operation period in Kostopil, Dubrovytsia, and Korets, the local population (mainly peasants) actively engaged in unequal trade exchanges with Jewish captives. In exchange for clothing, shoes, jewellery, and money, the peasants brought food to the Jews. When the money ran out, the Jews resorted to offering their own labour in exchange for food. Such interaction was much easier to arrange for prisoners of non-fenced ghettos in Korets and Dubrovytsia. The starvation in the ghetto was becoming the most terrible when its inhabitants were running out of valuables, which they could exchange for food, and the peasants were losing interest in bringing food. At the stage of ghetto liquidation, in all three towns, spontaneous plundering of the houses of the murdered Jews took place. Each time after the liquidation actions, the sales of Jewish property (mainly clothing, furniture, and real estate) started. The Nazi occupation authorities legalized the trade-in Dubrovytsia and Kostopil, which was carried out by town officials (they were mostly local Ukrainians). The beneficiaries of the trade were mainly neighbours of the Jews (Ukrainians and Poles) who lived in these towns and surrounding villages. In Korets, the district administration organized the sales of the property of the murdered Jews, and Ukrainian peasants from the surrounding villages took part in it. In addition to individuals, Ukrainian organizations (village branches of the “Prosvita” Society, Ukrainian schools, etc.) also took part in the purchase of furniture and houses of the Holocaust victims. Jews managed to escape from ghettos or places of execution and for some time to hide in the surrounding areas. In this case, their fate depended on the attitude of the local population. The residents of the surrounding villages displayed a wide variety of behaviour patterns while hiding victims outside the ghetto. In particular, peasants and locals could in rare cases hide victims without any material interest (the behaviour of rescuers), occasionally provide shelter or food and help Jews for some benefits (use of Holocaust victims as labour, unequal exchanges of food for tangible goods), hide for money or other valuables, deliver victims up to occupation authorities in exchange for material benefits (usually scarce in wartime goods such as kerosene, alcohol, salt, and sugar), or even be actively involved in identifying places of refuge of Jews for material dividends and minor career preferences. According to the Holocaust victims’ memoirs, many Ukrainian and Polish peasants developed various models of interaction with the Holocaust victims, guided by incentives for material gain. In some cases, it helped the victims to survive (assistance in exchange for material gain). In others, it led to disaster. Anyway, “righteous” behaviour was much less common than that which was motivated by economic motives.